Lotion Quality in Terms of Physical and Chemical Properties at Different ConcentrationsButterfly Pea Flower Extract - Ayu Putri MS; Diana Nurul Homaida; Dina Trianggaluh Fauziah; Neny Poerwahyuningrum (LPPM Universitas dr. Soebandi, 2026)
ABSTRACT Butterfly pea flowers were chosen because they contain active substances such as flavonoids and anthocyanins, which are known to have strong antioxidant properties and are suitable for use in topical products such as lotions. This study aimed to develop and assess the physical and chemical quality testing of lotion formulations derived from ethanol extract of butterfly pea flowers (Clitoria ternatea L.). Extraction was carried out using a maceration technique with 96% ethanol. Three different lotion formulations were made with various concentrations of butterfly pea flower extract: 0.5%, 1%, and 1.5%. Formulation assessment was carried out through physical and chemical quality examinations, which included organoleptic evaluation, homogeneity test, pH measurement, viscosity analysis, adhesion test, and spreadability assessment. The test results showed that each formulation met the physical and chemical quality standards required for topical products. The formulation containing 1.5% extract showed the greatest viscosity and adhesion, but had the lowest spreadability. Conversely, the formula with 0.5% extract showed the best spreadability despite having a lower viscosity. pH assessment confirmed that all formulations were within the skin-safe range (4.5–8). Changes in the concentration of ethanol extract from butterfly pea flowers affected the physical attributes of the lotion formulations, such as viscosity, spreadability, adhesion, and acidity. However, the acidity of the lotion formulations was still below the skin's acidity standards. Key words: Clitoria ternatea L., Lotion, Physical quality test, Chemical Quality test